Wired mobile phones: the case of community technology centers in favelas of Brazil*. Issue 3 (3rd July 2018) - Nemer, David
ABSTRACT: The growing spread of mobile phones and internet has some practitioners and scholars arguing about the possible irrelevance of community technology centers (CTCs) serving low-income communities. However, although mobile internet is making great strides, it does not yet substitute for public access; in actuality, mobile phones and computers at CTCs complement each other in providing those who face digital inequalities with a broader sociotechnical experience. In order to explore this problem, this paper explores this experience by investigating how favela residents appropriate mobile phones, posing the question, "how do marginalized populations perceive CTCs in the mobile internet era?" To address this question, I draw on a 10-month ethnography in the favelas of Vitória, Brazil which examines slum residents' uses of information and communication technologies (ICTs) such as computers and smartphones. Through this research, I demonstrate how marginalized people take advantage of smartphones and computers in a complementary way, using these ICTs to best meet their needs as they experience daily life in a relatively severe environment.